Pengaruh Komunikasi Informatif tentang Seks dan Seksualitas terhadap Pengetahuan Remaja - Neni Yulianita (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2000)
This is an experimental study on the effects of the oral and written informative communication on sex and sexuality. The experiment was conducted at SMA in Bandung, the first class students being the experiment subjects. From the population (340 students), 78 students were picked up at random. The subjects were divided at random into three groups: the